Hardiness of students with and without disabilities in war conditions - Ovcharenko, Olena (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2023)
Background. The purpose of the study is to theoretically and empirically investigate the peculiarities of the resilience of students with and without disabilities in the conditions of war.The relevance of the study is the formation of resilience in students with and without disabilities in war conditions, due to the fact that in war conditions students face trials that they have to overcome or adapt to, adapt to harsh living conditions, while maintaining mental and physical health at the expense of available resources, which are in short supply in times of crisis. Methods. An empirical study of resilience of students with and without disabilities was conducted using the resilience test, which is an adaptation of the Hardiness Survey developed by the American psychologist Salvatore Maddi. Results. The sample consisted of 60 students of the Open International University of Human Development "UKRAINE". According to the results of the study, it is stated that the values of indicators of the components of vitality (when compared with normative indicators) in students with and without disabilities are within the norm and are at an average level. Also, 50 % of students with disabilities have a low level of resilience compared to students without disabilities, who have 36,4 %. Among students without disabilities, the average level of vitality prevails, which is 40,9 %. Summing up, the values of indicators of the components of vitality (when compared with normative indicators) in students with and without disabilities are within the norm and are at an average level, which indicates that students with disabilities are almost no different from students without disabilities. Conclusions. We can say that the war in Ukraine has an effect on the decrease in the vitality index. Students do not feel safe, air alarms significantly affect the educational process, which either stops or continues in a state of anxiety, when everyone is already thinking about whether the cause of the alarm is a training take-off of a plane in enemy territory or a missile launch. Therefore, students cannot control their actions and have control over the situation and do not believe in their own strength. In connection with this, it is still more difficult for students with disabilities to overcome stressful conditions and adapt to the surrounding events. People with disabilities are always in a state of struggle, they always need to adapt to certain conditions and overcome life’s difficulties. Students without disabilities have lower indicators of sustainability of involvement and control compared to students with disabilities. In our opinion, students without disabilities are affected by the increased responsibility for loved ones and the fact that some students had to go to work and support their families, also male students belong to the category of possible mobilized, which is clearly a trigger for the underestimation of these indicators. But still, according to indicators of vitality and its components, students with disabilities are almost no different from students without disabilities. At the same time, in order to reduce tension, stress and exhaustion of student youth in the conditions of war, it is necessary to strengthen psychological support, which should be implemented in the institution of higher education to create safe, comfortable learning conditions. The psychological and physical health of students is a significant factor in successful self-realization.